Orbital misalignment of the super-Earth π Men c with the spin of its star - Kunovac Hodžić, Vedad; Triaud, Amaury H M J; Cegla, Heather M; Chaplin, William J; Davies, Guy R (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT Planet–planet scattering events can leave an observable trace of a planet’s migration history in the form of orbital misalignment with respect to the stellar spin axis, which is measurable from spectroscopic time-series taken during transit. We present high-resolution spectroscopic transits observed with ESPRESSO of the close-in super-Earth π Men c. The system also contains an outer giant planet on a wide, eccentric orbit, recently found to be inclined with respect to the inner planetary orbit. These characteristics are reminiscent of past dynamical interactions. We successfully retrieve the planet-occulted light during transit, and find evidence that the orbit of π Men c is moderately misaligned with the stellar spin axis with λ = − 24${_{.}^{°}}$0 ± 4${_{.}^{°}}$1 ($ψ = {26{_{.}^{°}} 9}^{+5{_{.}^{°}}8 }_{-4{_{.}^{°}}7 }$). This is consistent with the super-Earth π Men c having followed a high-eccentricity migration followed by tidal circularization, and hints that super-Earths can form at large distances from their star. We also detect clear signatures of solar-like oscillations within our ESPRESSO radial velocity time series, where we reach a radial velocity precision of ∼20 cm s−1. We model the oscillations using Gaussian processes (GPs) and retrieve a frequency of maximum oscillation, $ν _max{} = 2771^{+65}_{-60}\, μ Hz$. These oscillations make it challenging to detect the Rossiter–McLaughlin effect using traditional methods. We are, however, successful using the reloaded Rossiter–McLaughlin approach. Finally, in the appendix, we also present physical parameters and ephemerides for π Men c from a GP transit analysis of the full Transiting Exoplanet Survey Satellite Cycle 1 data.